All in the Family: How the APPs Regulate Neurogenesis - Lazarov, Orly; Demars, Michael P. (Frontiers in Neuroscience, 2012)
Recent intriguing evidence suggests that metabolites of amyloid precursor protein (APP), mutated in familial forms of Alzheimer’s disease, play critical roles in developmental and post-natal neurogenesis. Of note is soluble APPα (sAPPα) that regulates neural progenitor cell proliferation. The APP family encompasses a group of ubiquitously expressed and evolutionarily conserved, type I tansmembrane glycoproteins, whose functions have yet to be fully elucidated. APP can undergo proteolytic cleavage by mutually exclusive pathways. The subtle structural differences between metabolites generated in the different pathways, as well as their equilibrium, may be crucial for neuronal function. The implications of this new body of evidence are significant. Miscleavage of APP would readily impact developmental and post-natal neurogenesis, which might contribute to cognitive deficits characterizing Alzheimer's disease. This review will discuss the implications of the role of the APP family in neurogenesis for neuronal development, cognitive function and brain disorders that compromise learning and memory, such as Alzheimer’s disease.